METODE-METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA INDUSTRI 4.0 DALAM PERSPEKIF AL-QUR'AN - Muhammad Iqbal Yuriza; Lukmanul Hakim (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
The term Industry 4.0 was first used at the 2011 Hannover Fair from April 4-8. The term is used by the German government to take the industrial sector to the next level with the help of technology. Quoting the Forbes page, the fourth generation industrial revolution can be interpreted as the intervention of industrial intelligence and automation systems. It is data-driven through machine learning and artificial intelligence (AI) technologies. The Industrial Revolution 4.0 is based on the Internet as the main pillar, combining the online world with the industrial assembly line to realize the transformation of industrial improvement. Its relationship is in the world of Islamic education, so inevitably the digitalization of Islamic education becomes a mandatory domain in its development according to the words of Ali bin Abi Talib "Educate your children according to their time because they live in their time not in your time". in line with this then Fardhu 'ain for every practitioner of Islamic education to become aware of these developments, of course, they must still be based on the guidelines for life for every Muslim, namely the Al-Qur'an al-Karim. so in this paper the Koran is not a barrier in the current era of the Industrial Revolution 4.0. The Qur'an is not an obstacle to the path of progress but positions the Qur'an as the strongest and highest support in developing learning methods in the Industrial Revolution 4.0 era.